On Time Effect of Preschool Education: Social Analysis Based on CUCDS - Bohan Yan; Yongjun Feng; Ning Cai (Complexity)
Cognitive ability is an important aspect of children’s development, but there is still room for discussion about the impact of preschool education on children’s cognitive ability. Based on the data of China Urbanization and Children Development Survey (CUCDS) of Tsinghua University, this paper categorizes cognitive ability into Chinese language cognition and mathematical cognition. It is discovered that the impact of preschool education on children’s cognitive development differs depending on the cognitive ability and the length of time. In particular, preschool education has both short-term and long-term effects on children’s Chinese cognitive ability, while there is only a short-term effect on the development of children’s mathematical cognitive ability without long-term effect.